PENINGKATAN PENDAPATAN IBU-IBU DASAWISMA MELALUI PELATIHAN DAN PEMBUATAN PUPUK ORGANIK SERTA PENERAPANNYA PADA TANAMAN SAYURAN DI DUSUN KERANJANG, KECAMATAN WAYAME, KOTA AMBON - Kaya, Elizabeth; Puturuhu, Ferad; Putinella, June A. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
This community service activity aims to: increase the knowledge and skills of Dasawisma mothers in Keranjang hamlet in making Liquid Organic Fertilizer (POC) which is used to increase soil fertility in vegetable farming and increase family income after they can produce their own organic fertilizer and sell it as a side business. Keranjang Hamlet in Wayame Village is the location of this community service activity. Counseling and training for participants (mothers in Keranjang Hamlet), as well as application in the field are activity techniques used to achieve the expected results. Based on the results of the activity, there was an increase in knowledge about making POC by Dasawisma mothers because they produced POC products. The results of POC treatment to the soil using kale plants showed that the higher the POC dose, the higher the wet weight and height of the kale plants.